PERAN KEPUASAN PELANGGAN SEBAGAI PEMEDIASI PADA PENGARUH CITRA RESTORAN TERHADAP BEHAVIORAL INTENTION - Mukhlison, Ernawati & Sumarno Dwi Saputra (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2016)
The objective of the research are to analyses (1) effect of restaurant image to behavioral intentions, (2) effect of restaurant image to customer satisfaction, (3) effect customer satisfaction to behavioral intentions, (4) effect of restaurant image to behavioral intentions, through customer satisfaction as the mediating variable. Population on this research are all customer of restaurant “Bandeng Segar Mbak Mar” in Surakarta. The samples of this research consist of 100 respondent, taken with accidental sampling. Data collecting with questionnaire technique through validity and reliability test. To test the hypothesis, the researcher using the path analysis, meanwhile data processing in this research using SPSS program. The result reveals that (1) restaurant image have significance effect to behavioral intentions; (2) restaurant image have significance effect to customer satisfaction; (3) customer satisfaction have significance effect to behavioral intentions; (4) customer satisfaction is able to mediate the effect of restaurant image to behavioral intentions. The conclusion of this research that all hypothesis are supported.Keywords: restaurant image, customer satisfaction, behavioral intentions